ANALISIS ALIRAN FILSAFAT ILMU & ETIKA - Salma Yetti; Azmi Fitrisia; Ofianto Ofianto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The development of the philosophy of science over time. Discusses several schools of philosophy of science: materialism, dualism or realism, empiricism, rationalism, positivism, criticism, idealism, Renaissance, existentialism, phenomenology, pragmatism, and progressivism. This research is based on descriptive literature study, comparative analysis based on textual research. Philosophy of science develops from one school or schools to another. Ethics also teaches us to act more confidently in life. Ethics is needed as a guide to comply with established norms.Keywords: Philosophy of Science; Ethics